Building brand identity in the age of social media : emerging research and opportunities - Ekhlassi, Amir, 1979-; Niknejhad Moghadam, Mahdi, 1990-; Adibi, Amir Mohammad, 1991- (IGI Global, 2017)
"This book describes the concept of brand identity; examines managing brands by using social media; introduces brand building strategies in social media; explains creative strategy and the importance of content in social media; and describes the role of social media in different forms of brand building, and explains the impact of social media on brand loyalty"- Resumé vydavatele
Keywords: obchodní značky; internetový marketing; reklama a propagace; sociální média; brand name products; Internet marketing; advertising; social media; branding (marketing); elektronické knihy; monografie; electronic books; monographs